Network of Networks: Preliminary Lessons from the Antwerp Port Authority on Crisis Management and Network Governance to Deal with the COVID‐19 Pandemic. (30th August 2020) - van den Oord, Steven; Vanlaer, Niels; Marynissen, Hugo; Brugghemans, Bert; Van Roey, Jan; Albers, Sascha; Cambré, Bart; Kenis, Patrick
Abstract: In this article, the authors describe and illustrate what they call a "network of networks" perspective and map the development of a lead network for the Antwerp Port Authority that governed organizations and networks in the port community before and during the COVID‐19 pandemic. They find that setting a collective focus and selective integration are crucial in the creation and reproduction of an effective system to adequately deal with a wicked problem like the COVID‐19 pandemic. The findings on crisis management and network governance are used to engage practitioners and public policy planners to revisit the current design and governance of organizational networks within organizational fields that have been hit by the COVID‐19 pandemic.